WATER QUALITY ANALYSIS ON PHYTOPLANKTON ABUNDANCE AS A BIOINDICATOR OF MARINE WATER TROPHIC STATUS - Ayu Mariati Hutabarat; Munandar Munandar; Muhammad Rizal (Jurnal Perikanan Unram, 2024)
Phytoplankton is an organism that plays an important role as an oxygen producer and a measure of water pollution. Phytoplankton activity is strongly influenced by water quality parameters such as temperature, pH, light intensity, current speed, nitrate, phosphate, DO, BOD and salinity. However, studies on the analysis of water quality studies on phytoplankton abundance are still little implemented in Aceh waters. This study aims to analyze water quality, determine the type and abundance, diversity, uniformity, dominance of phytoplankton. Linear regression analysis was used to determine the relationship between environmental parameters on phytoplankton abundance, in the marine waters of Pulau Banyak District, Aceh Singkil Regency. This research was conducted in September-November 2024 in the waters of Baguk Island and Panjang Island, Pulau Banyak Subdistrict, Aceh Singkil Regency. Data collection using purposive sampling method based on the results of observations. From the results of the study obtained phytoplankton abundance in the waters of Baguk Island and Panjang Island amounted to 31.11 - 55.56 cells/L consisting of 28 genus which are divided into 5 classes namely Bacillariophyceae, Cyanophyceae, Dynophyceae, Oligotrichea, Zygnematophyceae. The ecological index in the waters of Baguk Island and Panjang Island consists of a diversity index (H') including the medium category, a uniformity index (E) including the high category and a dominance index (D) including the low category. Regression results show that the temperature parameter has a strong influence and relationship to phytoplankton abundance of 75.7%. While other parameters do not significantly affect phytoplankton. The waters of Baguk Island and Panjang Island are included in oligotrophic status and moderately polluted.